Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae) from the southern South American Transition Zone and boundaries: taxonomic overview with four new species - Cherman, Mariana A.; Basílio, Daniel S.; Mise, Kleber M.; Frisch, Johannes; Smith, Andrew B.t.; Almeida, Lúcia M. (Zootaxa, 2020)
The biodiversity of Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae: Diplotaxini) from the southern South American Transition Zone and boundaries is presented. Four new species are described: L. brachyclypeata Cherman, new species; L. lucialmeidae Cherman, new species; L. martinezi Cherman, new species; and L. maxillaricuspis Cherman, new species. The synonymy of L. flaveola Moser, 1924 (= L. kadleci Frey, 1970) is proposed. Lectotypes are designated for L. flavida Moser, 1918; L. pallidicornis Blanchard, 1851 (currently L. xanthocera Harold, 1869); and L. rufoflava Moser, 1918. Redescriptions are provided for all the species mentioned above plus L. calcarata Frey, 1970 and L. kunzteni Moser, 1921, as well as an identification key and updated geographical distributions to all species in the region. All species are present in the Monte province, except of L. kuntzeni (Andean provinces of Chile). Liogenys flavida and L. rufoflava have the broadest distribution, the latter here expanded to Paraguay and Chile.